A new genus and species of Heligmonellidae (Nematoda: Trichostrongylina) parasitic in Delomys dorsalis (Rodentia: Sigmodontinae) from Misiones, Argentina - Digiani, María Celina (2014)
Alippistrongylus bicaudatus gen. et sp. n. (Nematoda: Heligmonellidae) is described from the striped Atlantic forest rat, Delomys dorsalis (Hensel) (Rodentia: Sigmodontinae), from the province of Misiones in Argentina. The new genus and species is characterised by a synlophe of 21 unequal ridges in both sexes without a gradient in size, with two ridges weakly sclerotised and oriented perpendicularly in the dorsal left quadrant; males with a highly dissymmetrical bursa with a hypertrophied right lobe, and females with a dorsal conical appendage just posterior to the vulva, conferring a two-tailed appearance to the female worms.